Pengembangan Buku Ajar Berbasis Pengintegrasian Peerassessment Pada Model Pembelajaran Kooperatif Untuk Meningkatkan Keterampilan Sosial Peserta Didik - Siti Rabiatul Adawiyah; Nofisulastri Nofisulastri (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2019)
This research aimed to develop students’ book what integrate peer assessment into cooperative learning model, that it is valid and suitable to increase the student’s social skills. The kind of this research was development research that develop students’ book based on the characteristic of cooperative learning and was integrated an assessment technique that called peer assessment, students’ book development is done by using Dick and Carey model (2009). Students’ book validation is done by 3 validators with the results of validation was good category (3.4). The research data were analyzed descriptively, where the results showed that  the student’s social skills tended to increase  at every meeting. Based on the results of  research, it could be concluded that the students’ book developed were valid and suitable to be used in learning process to increase the student’s social skills.